Evaluation of anticoagulation with bivalirudin for heparin-induced thrombocytopenia during extracorporeal membrane oxygenation. Issue 8 (August 2022) - Hanna, Dylan J; Torbic, Heather; Militello, Mike; Strnad, Kyle; Krishnan, Sudhir; Hohlfelder, Ben
Introduction: Unfractionated heparin is the most commonly utilized anticoagulant in extracorporeal membrane oxygenation (ECMO) due to clinician familiarity, ease of reversal, and low cost compared to alternative agents. However, heparin's anticoagulant effect can be unpredictable and its use accompanies a risk of heparin induced thrombocytopenia (HIT). Successful use of bivalirudin as an alternative to heparin in non-HIT ECMO patients has previously been described. However, there is a paucity of data regarding its utilization in patients with confirmed HIT on ECMO. Methods: This single-center retrospective chart review at Cleveland Clinic Main Campus included 12 ECMO patients who were managed with bivalirudin for a new diagnosis of HIT. Descriptive statistical analyses were performed utilizing median with interquartile range and number with percent as appropriate. Results: Of the 12 patients included, median ECMO duration was 328.5 (218.8–502.1) h and venoarterial ECMO was the most common configuration. No patients experienced the primary outcome of in-circuit thrombosis while on bivalirudin. One patient developed a deep vein thrombosis 22.5 h after switching from heparin to bivalirudin. Major bleeding occurred during bivalirudin therapy in 8 (66.7%) patients. Conclusions: Overall, our study results suggest that bivalirudin is effective for the management of HIT and did not show evidence of in-circuit thrombosis. A high incidence of major bleeding was observed with bivalirudin use within this study. Clinicians should view bivalirudin as an acceptable agent for the treatment of HIT in the ECMO population, but must consider bleeding risk given the lack of effective reversal agents.